Congenital pouch colon associated with anorectal malformation: A rare anomaly of Asian Region - experience of Kurdish centre - Rossella Angotti; Qadir Qadir Mohamed Salih; Francesco Molinaro; Francesco Ferrara; Marina Sica; Edoardo Bindi; Mario Messina (Wolters Kluwer Medknow Publications, 2018)
Background: Congenital pouch colon (CPC) is an unusual malformation associated with anorectal malformations (ARMs) that are seen especially in Asia. The aim of this study was to analyse our series of CPC associated with ARM in our centre and report our experience based on the rarity of pathology. Materials and Methods: This is a retrospective study conducted at the Department of Paediatric Surgery in North Iraq. We identified patients from a prospectively kept database, including all patients managed between 1997 and 2014. Results: In total, 17 patients (3 females and 14 males) were included; all had CPC and high ARM; male:female ratio was 5.6:1. Two females had colo-vestibular fistula, 1 had a colo-cloacal fistula, all males had imperforate anus with colovesical fistula. Pre-operative diagnosis of CPC was made in eight patients (47%). Four patients (23.5%) had an incomplete pouch colon (Type III and IV), and 13 (76%) had complete pouch colon (Type I and II). All patients were managed with staged surgery. Mortality rate was 17.6% (3/17). Conclusions: CPC associated with ARM can be defined as 'Asian' complex malformation. Few cases are reported in Literature from Europe and USA. However, it is known that it is ever more frequent the collaboration between Asian and European surgeons (as in our study), so the suspicion should be considered in all patient high ARM who come from Asian region. We reviewed literature and report our experience of 15 years, after a retrospectively analysis, to share it and add our data to their reported.